HUBUNGAN UMUR, PARITAS DAN FREKUENSI MENYUSUI DENGAN PRODUKSI AIR SUSU IBU (ASI) DI KLINIK ANDRI KOTABANGUN - Peny Ariani; Putri Ayu Yessy Ariescha; Nur Mala Sari; Angelika Terulin (Jurnal Doppler, 2021)
Overall only 44% of newborns in the world get breast milk within the first hour of birth, even a few babies at the age of six months are breastfed exclusively. The purpose of this study is the relationship of age, parity and frequency of breastfeeding with the production of breast milk (breast milk) at The Andri Clinic in Kota Bangun in 2021. The type of research used in this study is correlated with the cross sectional approach. The samples in this study were taken by total polulation as many as 41 respondents. Data collection techniques are taken from primary data that is data obtained by giving questionnaires to nursing mothers. Based on the results of the study using chi-square test with a confidence level of 95% obtained the value of Ï = 0.030 in the age variable, the value Ï = 0.004 in the variable parity and Ï = 0.000 in the variable frequency of breastfeeding. The conclusion of this study is the relationship of age, parity and frequency of breastfeeding with the production of breast milk (breast milk). It is expected in all mothers in order to increase knowledge on how to increase the production of breast milk.